(untitled) (Tanzania Journal for Population studies and Development, 2021)
There is no doubt that climate change has significantly impeded poverty reduction and development efforts in many countries. Recent climate-related catastrophes have caused significant damages to developing countries and their citizens. This article analyses the nexus between climate change mitigation and its impact on Tanzania’s poverty reduction strategies. With the government’s decision to abandon poverty reduction strategies in 2011, it is vital to understand how these issues are mainstreamed in national plans. Drawing on extensive literature of secondary sources and official publications, the article demonstrates that, notwithstanding many promising features of the new national development plan, Tanzania has performed poorly within the overarching notion of mainstreaming climate change in its various national development plans. Findings further show that despite all these efforts made in previous climate change and poverty reduction strategies, Tanzania is still ill-prepared to face future climate change challenges. The article concludes that climate change issues are real and have already caused a significant setback to agricultural production and other productive sectors, posing a serious threat to human and food security. It recommends reconsidering mainstreaming climate change in development plans, adequate budgetary allocation, and establishing an effective National Adaptation Programme of Action (NAPA) to coordinate climate-risk information at national and local levels.